Working Memory Training and Cortical Arousal in Healthy Older Adults: A Resting-State EEG Pilot Study - Spironelli, Chiara; Borella, Erika (Frontiers in Aging Neuroscience, 2021)
The aim of the current pilot study was to test the gains of working memory (WM) training, both at the short- and long-term, at a behavioral level and the electrophysiological changes in resting-state EEG activity among older adults. Twenty-four older adults (from 64 to 75 years old) were randomly assigned to a training group (TG) or an active control group (ACG) in a double-blind, repeated-measures experimental design in which an open eyes, resting-state EEG recording, followed by a WM task – the Categorization Working Memory Span (CWMS) task – were collected before and after training, as well as at a 6-month follow-up session. At the behavioral level, medium to large Cohen’s d effect sizes were found for the TG in immediate and long-term gains to the WM criterion task, as compared with small gains for the ACG. Regarding intrusion errors committed in the CWMS – an index of inhibitory control representing a transfer effect – medium to large effect sizes for immediate and long-term gains emerged for the TG, as compared to small effect sizes for the ACG. Spontaneous high-beta/alpha ratio analyses in four regions of interest (ROIs) revealed no pre-training group differences. Significantly greater TG anterior rates, particularly in the left ROI, were found after training, with frontal oscillatory responses being correlated with better post-training CWMS performance in only the TG. The follow-up analysis showed similar results, with greater anterior left high-beta/alpha rates among TG participants. Follow-up frontal high-beta/alpha rates in the right ROI were correlated with lower CWMS follow-up intrusion errors in only the TG. The present findings are further evidence of WM training’s efficacy in enhancing older adults’ cognitive functioning and also their frontal oscillatory activity. Taken together, these results suggest that WM training also can be a promising approach toward fostering the so-called functional cortical plasticity in aging.